1996
DOI: 10.1007/bf00024581
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ethylene on growth and plant regeneration in callus cultures of Heliconia psittacorum L.f.

Abstract: The level of ethylene accumulated in morphogenic callus cultures of Heliconia psittacorum L.f. was only one quarter that of non-morphogenic cultures. The rate of ethylene production in the morphogenic callus cultures during early stages of differentiation of protocorm-like bodies leading to plantlet regeneration was lo-fold higher than that during callus proliferation. In cultures sealed with gastight serum caps, fresh weight gain was reduced 2-to 3-fold compared to those that were closed with Kaput&). Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The effects of ethylene on explant growth and morphogenesis seem to be species-specific. This hormone may promote organogenesis or embryogenesis in some plant species (Kumar et al, 1987(Kumar et al, , 1996Dimasi-Theriou et al, 1993), while in others it may have an inhibitory effect (Chraibi et al, 1991;Plus et al, 1993;Burnett et al, 1994). Although the use of ethylene inhibitors in in vitro cultures has produced contradictory results (Krikorian, 1995), several reports (Perl et al, 1988;Hulme et al, 1992;Moilers et al, 1992) have demonstrated the suitability of STS as an inhibitor of ethylene action.…”
Section: Effect Of Silver Thiosulfate On Bud Inductionmentioning
confidence: 97%
“…The effects of ethylene on explant growth and morphogenesis seem to be species-specific. This hormone may promote organogenesis or embryogenesis in some plant species (Kumar et al, 1987(Kumar et al, , 1996Dimasi-Theriou et al, 1993), while in others it may have an inhibitory effect (Chraibi et al, 1991;Plus et al, 1993;Burnett et al, 1994). Although the use of ethylene inhibitors in in vitro cultures has produced contradictory results (Krikorian, 1995), several reports (Perl et al, 1988;Hulme et al, 1992;Moilers et al, 1992) have demonstrated the suitability of STS as an inhibitor of ethylene action.…”
Section: Effect Of Silver Thiosulfate On Bud Inductionmentioning
confidence: 97%